2022
DOI: 10.1039/d2qm00347c
|View full text |Cite
|
Sign up to set email alerts
|

A novel quaternized carbon dot–papain complex for the double-target anti-biofilm activity and visualization-ratio fluorescence dual-mode detection of H2O2

Abstract: Since biofilm infections could cause chronic diseases and drug resistance, posing serious threat to human health, the development of antibiofilm nanomaterials has attracted the interest of researchers. In this paper,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…The authors reported that CDs at medium concentrations inhibited biofilms, while at high concentrations they eradicated biofilms . Quaternized CD–papain complexes showed excellent inhibition of S. aureus biofilms at a minimum concentration of 20 μg/mL via mechanisms of membrane, DNA, and protein degradation and papain-based hydrolysis of proteins . Aminoguanidine CDs (AG/CA CDs) prepared by Otis et al in 2019 were reported to exhibit excellent bactericidal and anti-biofilm properties on P. aeruginosa .…”
Section: Carbon Dots In Biofilm Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors reported that CDs at medium concentrations inhibited biofilms, while at high concentrations they eradicated biofilms . Quaternized CD–papain complexes showed excellent inhibition of S. aureus biofilms at a minimum concentration of 20 μg/mL via mechanisms of membrane, DNA, and protein degradation and papain-based hydrolysis of proteins . Aminoguanidine CDs (AG/CA CDs) prepared by Otis et al in 2019 were reported to exhibit excellent bactericidal and anti-biofilm properties on P. aeruginosa .…”
Section: Carbon Dots In Biofilm Treatmentmentioning
confidence: 99%
“…102 Quaternized CD− papain complexes showed excellent inhibition of S. aureus biofilms at a minimum concentration of 20 μg/mL via mechanisms of membrane, DNA, and protein degradation and papain-based hydrolysis of proteins. 111 Aminoguanidine CDs (AG/CA CDs) prepared by Otis et al 113 in 2019 were reported to exhibit excellent bactericidal and anti-biofilm properties on P. aeruginosa. Their results revealed dosedependent inhibition of bacterial growth with complete inhibition of growth at 0.5 mg/mL AG/CA CD concentration.…”
Section: Carbon Dots In Biofilm Treatmentmentioning
confidence: 99%